A forgotten class of efficient marine fluorophores. Structural and photophysical properties of parazoanthoxanthins. (February 2021) - Benassi, Enrico; Benassi, Andrea
Abstract: Zoanthoxanthins and derivatives are rare cases of nitrogen-containing, polycyclic pigments discovered in colonial anthozoans of the family Zoanthidea in the 1970s. These compounds are characterised by intense fluorescence and acidochromism. However, many structural and photophysical aspects of these molecules remain unexplained. This investigation is the first attempt to provide a deeper understanding on the electronic and photophysical properties by means of quantum chemical methods. Two among the most diffused examples of parazoanthoxanthins have been chosen as a study case. The problem of the complex tautomerism these molecules undergo has been addressed, along with the protonation in acidic environment. The electrical properties and the topological features of the ground state have been investigated in details, revealing an environmental sensitive, quadrupolar nature of the investigated systems. A specific protocol has been designed to efficiently describe the excited electronic states in solution, which provided a good match with the experimental data. A particular attention was dedicated to explore the potential energy hypersurface of S 1, which revealed to possess one or two stable minima, dependently of the type of molecular system, the environmental conditions and the position of the protons. These fluorophores constitute a class of potentially promising molecular systems with tuneable photophysical properties. Graphical abstract: Image 1 Highlights: The problem of the complex tautomerism and protonation was addressed. These molecules revealed to be quadrupolar in nature. An efficient strategy to explore the excited states was designed. S 1 may possess two minima, one flat and emissive, the other twisted and dark.